Review of methods for enrichment of phosphate raw materials in the world - Raiymbekov, Y.B.; Besterekov, U.; Abdurazova, P.A. (KSU Publ., 2020)
With the development of the global economy, the consumer market for phosphorus-containing products is growing. All existing deposits of rich phosphorites are being depleted. In this regard, there is a need to involve in the production of low-grade phosphorites and substandard phosphate raw materials, which are currently little studied and are not used. For the processing of substandard phosphorites, there is a need for new methods for improving and enriching low-grade ores and removing impurities as much as possible in order to increase the content of the target components and improve the suitability for processing. The article provides modern information about the processes of enrichment of phosphorites in different countries. This information is fundamental for further research on the enrichment of Karatau phosphorites. The review is made mainly of two methodsflotation (applicable for silicate phosphates) and the use of organic acids (for carbonate substances). The mechanisms of separation of substances during flotation enrichment and decomposition of carbonate minerals using of organic acids are described. The advantages and disadvantages of each method are considered. It is established that the choice of a certain method is determined by the mineralogical structure and chemical composition of phosphorites.
Әлемдегі фосфат шикізатын байыту әдістеріне шолу
Обзор методов обогащения фосфатного сырья в мире
Keywords: phosphorite; deposit; chemical industry; production; enrichment; flotation; substandard raw materials; low-grade ores